2017
DOI: 10.1007/s13205-016-0579-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from cell suspension culture in Saccharum officinarum L. and ascertaining of genetic fidelity through RAPD and ISSR markers

Abstract: The aim of this study was to produce sugarcane plantlets from cell suspension culture and study its genetic fidelity using molecular markers. The study was carried out using sugarcane varieties Co 86032 and Q117. Callus cultures of both the varieties were optimized using six different callus induction media. After screening the growth response of callus on six different callus induction media, it was observed that medium no. VI supplemented with 500 mg l−1 of each PVP, Casein hydrolysate and MES buffer showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…The results of the cluster analysis showed that the mother plant samples (control) and the effects of in vitro propagation in one variety had a high level of genetic similarity, which was more than 0.94 except for the PS 862 genotype (Figure 1). The similarity coefficient found in the current study was 0.94 higher than that previously reported by Thorat et al (2017), which analyzed two varieties of sugarcane that produced a genetic similarity coefficient of 0.90 and 0.87, respectively. Also higher than the study of Tiwari et al (2011), which detected a genetic similarity coefficient of more than 85% based on molecular tests using SSR markers.…”
Section: Genetic Stability Of Sugarcane Varieties During Subculturescontrasting
confidence: 87%
“…The results of the cluster analysis showed that the mother plant samples (control) and the effects of in vitro propagation in one variety had a high level of genetic similarity, which was more than 0.94 except for the PS 862 genotype (Figure 1). The similarity coefficient found in the current study was 0.94 higher than that previously reported by Thorat et al (2017), which analyzed two varieties of sugarcane that produced a genetic similarity coefficient of 0.90 and 0.87, respectively. Also higher than the study of Tiwari et al (2011), which detected a genetic similarity coefficient of more than 85% based on molecular tests using SSR markers.…”
Section: Genetic Stability Of Sugarcane Varieties During Subculturescontrasting
confidence: 87%
“…Chamomile is known to exist in more than 120 constituents ( McKay & Blumberg, 2006 ), imparting anticancer ( Shoeb et al, 2001a ), analgesic, anti-convulsive, carminative, anti-seizure ( Ghanavatifard, Mohtadi & Masoumiasl, 2018 ), anti-inflammatory, antibacterial, sedative, immune booster, anti-allergic, anti-inflammatory, antiseptic and smooth muscle relaxant properties ( Sotiropoulou, Megremi & Tarantilis, 2020 ). Increased use of herbal medicines has threatened the survival of a large number of medicinally important plant species ( Abbas et al, 2018 ; Mumtaz et al, 2017 ; Thorat et al, 2017 ). However, development of sustainable crop production technologies as well as conservation strategies is inevitable ( Abbas et al, 2020 ; Tahir ul Qamar & Khan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it did not mean that any mutation of the somatic embryo regeneration system in Chinese chestnut did not occur. Many studies indicated that somaclonal variation occurred during plant regeneration, such as coffee and sugarcane (Landey et al 2015;Thorat et al 2017). No variations were observed during somatic embryogenesis and regeneration in Chinese chestnut, which may be due to a very limited population detected or that the loci identified of genetic fidelity were not sufficient, as only 24 pairs of SSR primers and two gene fragment sequences were identified.…”
Section: Assessment Of Somaclonal Variationmentioning
confidence: 99%